THE INFLUENCE OF CIVIC EDUCATION VIDEO MEDIA WITH SCIENTIFIC APPROACH AGAINTS ANTI-CORRUTION STUDENTS ATTITUDES AT SENIOR HIGH SCHOOL 8 BANDUNG - Prayoga Bestari, Iqbal Arpannudin, Aim Abdulkarim, (Department of Civic Education, 2015)
The Eradiration of corruption through educational approach by reason that the anti-corruption movement in Indonesia is not maximized. Learning the values of anti-corruption in schools using instructional media video with the scientific approach is expected to grow passion to learn and give rise to the same perception of the dangers of corruption, anti-corruption values are instilled and changes in students' anti-corruption attitudes. This study used a quasi-experimental method possible to see the extent of the effect of the use of video media with a scientific approach to anti-corruption attitudes of students. The results showed there were differences in the anti-corruption attitudes among students in the experimental class that uses the medium of video with grade control with conventional learning on learning Citizenship Education.Â